Enhancing student learning and engagement with object-oriented block-based programming tool - Chin, Xavier Jia Le (2024)
Technologies have been adopted and integrated into various aspects of life, including education and learning. Gamified learning is effective to promote student learning and motivations. Object-Oriented Programming (OOP) is a fundamental topic taught to university students, and in certain countries, it is introduced as an enrichment course for younger students. It is beneficial to develop young students on the interests in software programming. Equipping younger students with essential programming skills will be helpful and better prepare them to excel in the digital age in the future. This research leverages the benefits of gamification to enhance student engagement by developing an educational game for teaching OOP. The developed educational visual programming tool simplifies complex OOP concepts and engagingly presents them through the medium of a game. It provides an alternative learning approach to visualizing and understanding OOP. The study yielded positive results, with improved test scores and a more consistent performance. It highlights the effectiveness of this approach in teaching OOP. The positive feedback from students regarding their enjoyment of gameplay also shows the potential of gamified learning in enhancing engagement.